THE EVALUATION OF OCCUPATIONAL RISKS AS A SUSTAINABLE DEVELOPMENT FACTOR OF THE INDUSTRIAL ENTERPRISES ECONOMY - A. S. Sokolitsyn; I. I. Kovalenko (Дискурс)
The article considers the interrelation between the occupational risks level and the stability of the industrial enterprises development. Occupational risks were assessed using the occupational injuries analysis and data on their economic damage at the enterprises of the Russian Federation for a ten-year period from 2006 to 2016. The sustainability of industrial enterprises development is examined considering two aspects, product competitiveness and labor productivity. A contradiction has been revealed between the decline in labor productivity and product competitiveness and the statistical reduction in the number of registered workplace accidents. This contradiction makes it difficult to estimate the real economic damage from occupational injuries. The tendency of the labor force to redistribute from production sectors characterized by high occurrence rate of industrial injuries to the non-productive sectors is revealed, which negatively affects the technological and innovative potential of Russian industrial enterprises.